It's all about timing: An electrophysiological examination of feedback-based learning with immediate and delayed feedback. (May 2017) - Arbel, Yael; Hong, Lucia; Baker, Travis E.; Holroyd, Clay B.
Abstract: Feedback regarding an individual's action can occur immediately or with a temporal delay. Processing of feedback that varies in its delivery time is proposed to engage different brain mechanisms. f MRI data implicate the striatum in the processing of immediate feedback, and the medial temporal lobe (MTL) in the processing of delayed feedback. The present study offers an electrophysiological examination of feedback processing in the context of timing, by studying the effects of feedback timing on the feedback-related negativity (FRN), a product of the midbrain dopamine system, and elucidating whether the N170 ERP component could capture MTL activation associated with the processing of delayed feedback. Participants completed a word-object paired association learning task; they received feedback 500 ms (immediate feedback condition) following a button press during the learning of two sets of 14 items, and at a delay of 6500 ms (delayed feedback condition) during the learning of the other two sets. The results indicated that while learning outcomes did not differ under the two timing conditions, Event Related Potential (ERPs) pointed to differential activation of the examined ERP components. FRN amplitude was found to be larger following the immediate feedback condition when compared with the delayed feedback condition, and sensitive to valence and learning only under the immediate feedback condition. Additionally, the amplitude of the N170 was found larger following the delayed feedback condition when compared with the immediate feedback condition. Taken together, the findings of the present study support the contention that the processing of delayed feedback involves a shift away from midbrain dopamine activation to the recruitment of the MTL. Highlights: FRN larger following immediate feedback when compared with delayed feedback. FRN sensitive to valence and learning only under the immediate feedback condition. Amplitude of the N170 larger following delayed feedback when compared with immediate feedback.